Inhibition of BMP signaling in P-Cadherin positive hair progenitor cells leads to trichofolliculoma-like hair follicle neoplasias - Kan Lixin (Journal of Biomedical Science, 2011)
Abstract Background Skin stem cells contribute to all three major lineages of epidermal appendages, i.e., the epidermis, the hair follicle, and the sebaceous gland. In hair follicles, highly proliferative committed progenitor cells, called matrix cells, are located at the base of the follicle in the hair bulb. The differentiation of these early progenitor cells leads to specification of a central hair shaft surrounded by an inner root sheath (IRS) and a companion layer. Multiple signaling molecules, including bone morphogenetic proteins (BMPs), have been implicated in this process. Methods To further probe the contribution of BMP signaling to hair follicle development and maintenance we employed a transgenic mouse that expresses the BMP inhibitor, Noggin, to disrupt BMP signaling specifically in subset of hair follicle progenitors under the control of neuron specific enolase (Nse) promoter. We then studied the skin tumor phenotypes of the transgenic mice through histology, immunohistochemistry and Western Blotting to delineate the underlying mechanisms. Double transgenic mice expressing BMP as well as noggin under control of the Nse promoter were used to rescue the skin tumor phenotypes. Results We found that the transgene is expressed specifically in a subpopulation of P-cadherin positive progenitor cells in Nse-Noggin mice. Blocking BMP signaling in this cell population led to benign hair follicle-derived neoplasias resembling human trichofolliculomas, associated with down-regulation of E-cadherin expression and dynamic regulation of CD44. Conclusions These observations further define a critical role for BMP signaling in maintaining the homeostasis of hair follicles, and suggest that dysregulation of BMP signaling in hair follicle progenitors may contribute to human trichofolliculoma.